DUKUNGAN KELUARGA DAN KEKAMBUHAN PASIEN RESIKO PERILAKU KEKERASAN DI RSJD Dr. AMINO GONDOHUTOMO PROPINSI JAWA TENGAH - Diyan Yuli Wijayanti (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Violence is one of the symtomps in patients with severe mental disorder. Medical recordinDr. Amino Gondohutomo hospital 2013th,68% patient with severe mental disorder wererelapsed and rehospitalized with violence. The aim of this study was toinvestigaterelathionship between family care support withfrequency of relapse in patientswith nursing diagnosed of Risk of Violence inDr. Amino Gondohutomo mental hospital ofcentral java. The research method was descriptive correlation. The sample were mainnursery care giver. The data was gathered by 2 questionnaire: family supportandfrequency of relapse. The amount of samples were78 determined by consecutivesampling method. Data analized was univariatewithfrequency distribution and normalitydata test, while bivariatedata analizedused was one way anova to find out therelathionsipbetween family care support with frequency of relapse. Result showed that55,1% of family gaveless support. 42,3% patientsrelapsedand rehospitalized 2 times,30,8% relapsed more than 2 times and 26,9% relapsed justonce. One way anova showedthat p-Value was 0,45 (p-value > 0,05), meaning thatthere’s no relathionshipbetweenfamily care support with frequency of relapse in patients with Risk of Violence. Therecomendationwasthatfamily should be supplied of knowledge of mental health andnursing carefor violence, so that family can give more support especially in afectiveandemosional support